HOW THE ROLE OF CUSTOMER REVIEWS AND CUSTOMER RATINGS ON PURCHASING DECISIONS ON THE TIKTOK SHOP FASHION APPLICATION AMONG UMB STUDENTS - Mogi Amano; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to analyze the role of customer reviews and customer ratings on purchasing decisions on Tiktok shop fashion application among UMB students. The success of Tiktok shop platform not only depends on product availability but is also influenced by factors such as reviews and customer ratings which play an important role in shaping consumer perceptions. This study uses a quantitative analysis method by collecting data through an online survey to Tiktok shop users among UMB students. The research sample consists of consumers who have made transactions on the platform. The collected data were analyzed using statistical techniques such as regression to explore the relationship between the variables of reviews and customer ratings with purchasing decisions. This study concludes that customer reviews and customer ratings have a big role in purchasing decisions on TikTok Shop Fashion, especially among UMB students. Customer reviews and ratings contribute significantly to shaping consumers' perceptions of products, which ultimately influence their decision to buy. These results confirm the importance of TikTok Shop management's attention to service and product quality to increase positive reviews and high ratings from customers. In addition, these findings provide valuable insights for the development of e-commerce strategies to understand and fulfill consumer needs and preferences.